Answer:
Step-by-step explanation:
a/7+b
You simply have to use the values provided in the equation given. If a=49 and b=7 you have
49/7+7, since 49/7=7 you have
7+7 which equals
14
A)
<span>|x + y = 5 </span>
<span>|2x - y = 7; </span>
<span>b) </span>
<span>|2x + y = 5 </span>
<span>|x - y = 2 </span>
<span>c) </span>
<span>|3x + y = 6 </span>
<span>|4x - 3y = -5 </span>
<span>d) </span>
<span>|1/(x - 1) = y - 3 </span>
<span>|x - y = -2 </span>
<span>e) </span>
<span>|(9x + 4y)/3 - (5x - 11)/2 = 13 - y </span>
<span>|13x - 7y = -8 </span>
<span>Answer: </span>c<span> and </span>e<span> has solution (1; 3)</span>
![y = 2 {x}^{2} - 3](https://tex.z-dn.net/?f=y%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20-%203)
![\huge\underline\mathtt\colorbox{cyan}{Explanation thing:}](https://tex.z-dn.net/?f=%5Chuge%5Cunderline%5Cmathtt%5Ccolorbox%7Bcyan%7D%7BExplanation%20thing%3A%7D)
Using hit and trial, you van find it pretty easily-
- Putting x=0, we get y=-3
- Putting x=1, we get y=-1
- Putting x=2, we get y=5
You can try it for yourself as well, for me, I couldn't find any other option appropriate.
Answer:
3.25
Step-by-step explanation: